Demographics and the Behavior of Interest Rates. Issue Volume 64:Issues 4(2016) (November 2016) - Favero, Carlo; Gozluklu, Arie; Yang, Haoxi
Abstract Interest rates are very persistent. Modeling the persistent component of interest rates has important consequence for forecasting. Factor models of the term structure are restricted VAR models that project over a long-horizon the one-period risk-free rate to obtain yields at longer horizon as the sum of the expected future monetary policy and the term premia. The included factors are typically mean reverting and the equilibrium real rates are considered constant (think, for example, of the standard Taylor rule), partial adjustments to equilibrium yields are then used to rationalize the persistence in the observed data. As a result, the empirical models feature a very high level of persistence that makes long-horizon predictions inherently inaccurate. This paper relates the common persistent component of the U.S. term structure of interest rates to the age composition of population. The composition of age structure determines the equilibrium rate in the monetary policy rule and therefore the persistent component in one-period yields. Fluctuations in demographics are then transmitted to the whole-term structure via the expected policy rate components. We build an affine term structure model (ATSM) which exploits demographic information to capture the dynamics of yields and produce useful forecasts of bond yields and excess returns that provide economic value for long-term investors.